Multi-time scale optimization scheduling of microgrid considering source and load uncertainty - Hou, Jianmin; Yu, Weijie; Xu, Zhihao; Ge, Quanbo; Li, Zhi; Meng, Ying (Electric power systems research, 2023)
•A multi-time scale optimal scheduling framework is proposed for microgrid scheduling to deal with the uncertainty of source and load.•A two-stage distributionally robust model is constructed to improve the robustness of the day-ahead scheduling plan.•The distributed model prediction control method is used to maintain the smooth power of contact lines.•The proposed multi-time scale scheduling method can achieve robust and economic operation of the microgrid. With the increase of renewable energy penetration in microgrid and the stochasticity of customer load, microgrid faces new difficulties in maintaining the smooth power of contact lines and system economy when achieving optimal scheduling. In order to balance the accuracy, economy and robustness of microgrid scheduling better, a multi-time scale optimal scheduling strategy for microgrids considering the uncertainty of source and load is proposed. In the day-ahead scheduling stage, a two-stage distributionally robust optimal scheduling model is established with the objective of minimizing the comprehensive day-ahead scheduling cost of the microgrid, and the optimal day-ahead scheduling solution is found under the probability distribution of the worst scenario. In the intra-day scheduling stage, based on the prediction value of source and load with higher accuracy, a distributed model predictive control method is used to build an intra-day rolling optimization and real-time adjustment optimal scheduling model, which ensures the effective implementation of the day-ahead plan and fully suppresses power fluctuation of the contact line. The simulation results show that the proposed multi-time scale optimal scheduling method can not only maintain the smooth power of contact lines, but also achieve robust and economic operation of the microgrid.